Lung volume reduction surgery in selected patients with emphysema and pulmonary hypertension. (12th March 2018) - Caviezel, Claudio; Aruldas, Carlson; Franzen, Daniel; Ulrich, Silvia; Inci, Ilhan; Schneiter, Didier; Weder, Walter; Opitz, Isabelle
Abstract: OBJECTIVES: Pulmonary hypertension (PH) is considered a contraindication for lung volume reduction surgery (LVRS). Because, it has been reported that endobronchial lung volume reduction may have a beneficial effect without increased mortality in patients with emphysema and PH, we evaluated its effect on PH in patients undergoing LVRS. METHODS: From January 2014 until June 2016, 119 LVRSs were performed at Zurich University Hospital. PH was a contraindication for patients with homogeneous emphysema but was acceptable for those with heterogeneous emphysema. Thirty patients underwent echocardiography before and after LVRS, 10 of whom had preoperative systolic pulmonary artery pressures >35 mmHg and 20 of whom had normal systolic pulmonary artery pressure. The effect of LVRS on pulmonary artery pressure, lung function and survival was analysed. RESULTS: Ninety-day mortality for all 30 patients was 0, and the postoperative course did not differ significantly between the 2 groups. In patients with PH, the median systolic pulmonary artery pressure decreased from 41 mmHg [interquartile range (IQR) 39–47] to 37 mmHg (IQR 36—38, P  = 0.04). These patients had an improvement of forced expiratory volume in 1 s from the median 27% predicted (IQR 23–34) to 33% (IQR 28–40, P  = 0.007) 3 months postoperatively. CONCLUSIONS: If further confirmed in other cohorts, mild to moderate PH may no longer be considered a contraindication for LVRS in patients with heterogeneous emphysema.